Funktionaalisten elintarvikkeiden klusteri: Esiselvitys - Hannu Hernesniemi (The Research Institute of the Finnish Economy (ETLA), 2004)
– Functional foods are the fastest growing sector of food industry. The average annual growth rate in functional foods is 7 per cent, whereas the total industry grows at the rate of 1-2 per cent. For the Finnish food industry functional foods represent a strategic area of growth, which can enable companies to cope with international competition. Taking into account the small size of economy Finland is one of the leading countries in functional food production in Europe. As many as 100 functional foods have been developed and introduced to the market. Research in this field began quite early in Finland, producing commercial applications in answer to national diseases (fructose for diabetes, xylitol for caries, benecol for heart diseases) much before functional foods became common as business ideas. Intensive research, interdisciplinary connections and contacts with industry have been an important competitive factor. There is a possibility of an emerging cluster formed by food industry, related industrial sectors, raw material production and research. This cluster would continuously generate competitive advantages. This, however, requires many improvements: Ground rules for functional food business must be set and unified both on the national and the EU level, which makes it easier to enter the market. It is necessary to create the prerequisite for exports and international operations of companies and to invest in research. On the international scale even the biggest Finnish companies are relatively small, but they can become leaders in niche products. It is necessary to support new SME's and their switch to functional production. They need help in utilizing research results, clinical testing of products, product development and experimental production, and initial marketing.
Keywords: 330; Finland; food industry; functional food; competitive edge